Lsr2 Is an Important Determinant of Intracellular Growth and Virulence in Mycobacterium abscessus - Le Moigne, Vincent; Bernut, Audrey; Cortès, Mélanie; Viljoen, Albertus; Dupont, Christian; Pawlik, Alexandre; Gaillard, Jean-Louis; Misguich, Fabienne; Crémazy, Frédéric; Kremer, Laurent; Herrmann, Jean-Louis (Frontiers in Microbiology, 2019)
Mycobacterium abscessus, a pathogen responsible for severe lung infections in cystic fibrosis patients, exhibits either smooth (S) or rough (R) morphotypes. The S-to-R transition correlates with inhibition of the synthesis and/or transport of glycopeptidolipids (GPLs) and is associated with an increase of pathogenicity in animal and human hosts. Lsr2 is a small nucleoid-associated protein highly conserved in mycobacteria, including M. abscessus, and is a functional homologue of the heat-stable nucleoid-structuring protein (H-NS). It is essential in Mycobacterium tuberculosis but not in the non-pathogenic model organism Mycobacterium smegmatis. It acts as a master transcriptional regulator of multiple genes involved in virulence and immunogenicity through binding to AT-rich genomic regions. Previous transcriptomic studies, confirmed here by quantitative PCR, showed increased expression of lsr2 (MAB_0545) in R morphotypes when compared to their S counterparts, suggesting a possible role of this protein in the virulence of the R form. This was addressed by generating lsr2 knock-out mutants in both S (Δlsr2-S) and R (Δlsr2-R) variants, demonstrating that this gene is dispensable for M. abscessus growth. We show that the wild-type S variant, Δlsr2-S and Δlsr2-R strains were more sensitive to H2O2 as compared to the wild-type R variant of M. abscessus. Importantly, virulence of the Lsr2 mutants was considerably diminished in cellular models (macrophage and amoeba) as well as in infected animals (mouse and zebrafish). Collectively, these results emphasize the importance of Lsr2 in M. abscessus virulence.